The New Lexicon Webster's dictionary of the english language. (Chicago : Lexicon Publication, 1989)
A library of information in one single volume. With more than 170,000 entries, this dictionary is uncomplicated but scholarly and comprehensive.
Preface -- Staff -- History of the English Language -- Languages of the world -- Guide to the Use of the Dictionary -- Editorial Abbreviations -- Pronunciation Key -- Dictionary of the English Language -- Flags of the world -- The presidency.
Keywords: DICTIONARIES